The unknown soldier the story of the missing of the Great War - Hanson, Neil (Corgi, 2007)
Drawing on unpublished letters and diaries, this work has resurrected the lives and experiences of three unknown soldiers - a Briton, a German and an American. This work shows the terrible reality of warfare. It explains that each soldier lives on in the memory of his family to this day. They stand at the head of a ghost army three million strong.